Implementation of ukhuwah values in the form of religious moderation in indonesia in the perspective of the qur'an - R Def Mochtar Hassanusi (Balai Diklat Keagamaan Ambon, 2022)
This article generally discusses the implementation of ukhuwah values ​​in the form of religious moderation in Indonesia from the perspective of the Koran. In more detail, the implementation of these values ​​is further elaborated into several aspects, including uncovering the factors that cause inter-religious conflict in Indonesia, the values ​​of ukhuwah in Islam, the implementation of ukhuwah values ​​in the form of moderation in religion in Indonesia, the form of implementation ukhuwah values ​​in the form of the madinah charter and their relevance in the life of religious moderation in Indonesia.